2020
DOI: 10.21203/rs.3.rs-90452/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher perceived risk of COVID-19 pandemic, higher concern for climate change: evidence from a longitudinal study in China

Abstract: COVID-19 is raging globally taking a huge toll on public health. Although there seems to be a silver lining regarding mitigation of climate change given decreased emission of greenhouse gases during the pandemic, climate disruption actually constantly keeps apace. Therefore, it is important for the public to maintain alert to climate change amid the devastating pandemic. The current longitudinal study made a preliminary exploration of the relationship between public risk perception of the pandemic and climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Finally, and most importantly, the results from this study empirically supported the use and the focal role played by the risk perception of COVID-19 construct in predicting (future) proenvironmental travel behavior. This is a novel construct recently introduced by Dryhurst et al (2020) to predict people's adoption of protection and preventive health behavior and was more recently adapted and used to examine people's post-COVID-19 concerns in relation to climate change and the state of the environment (Gong & Sun, 2020) and people's trust and future behavior intentions in relation to staying at green hotels (Jian et al, 2020). Our results show that this construct can be extended and further used to predict/explain changes in people's behavior as a consequence of the COVID-19 pandemic in and across different contexts, including predicting their pro-environmental travel behavior.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, and most importantly, the results from this study empirically supported the use and the focal role played by the risk perception of COVID-19 construct in predicting (future) proenvironmental travel behavior. This is a novel construct recently introduced by Dryhurst et al (2020) to predict people's adoption of protection and preventive health behavior and was more recently adapted and used to examine people's post-COVID-19 concerns in relation to climate change and the state of the environment (Gong & Sun, 2020) and people's trust and future behavior intentions in relation to staying at green hotels (Jian et al, 2020). Our results show that this construct can be extended and further used to predict/explain changes in people's behavior as a consequence of the COVID-19 pandemic in and across different contexts, including predicting their pro-environmental travel behavior.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Risk perception of COVID-19 (see Dryhurst et al, 2020) will also be incorporated into the model. Initially, this construct was used to explain the effect of COVID-19 on people's adoption of preventive public health measures (Dryhurst et al, 2020), as well as examine COVID-19's effect on people's concerns about climate change and the state of the environment (Gong & Sun, 2020), and in the tourism context, to examine how fear perception of COVID-19 affects travelers' trust and future behavior intentions to stay at green hotels (Jian et al, 2020). This justifies the use of the latter construct (risk perception of COVID-19) alongside NAM and economic sacrifice model to examine the effect of the pandemic on future pro-environmental travel behavior (PETB), whereas it is assumed that the higher the perceived risks (to both the individual and their acquaintances and to the people/planet as a whole), the more likely travelers are to worry about environmental problems that might exacerbate future pandemics, the greater the sacrifices they will be willing to accept, and the more willing they will be to make more environmentally conscious travel choices, to prevent such outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies on youth and young adults in the United Kingdom and Germany, it could be demonstrated that the Covid-19 pandemic and climate change are both associated with distress but evoke different emotional reponses [ 34 , 35 ]. Likewise, it could be demonstrated in another study in UK residents on worries related to the Covid-19 pandemic and climate change that although people have no finite pool of worries, different stressor groups may have differential behavioral effects [ 36 ] Other studies, for example from China, could demonstrate that worries in relation to different stressor groups can even fuel each other [ 37 ] Thus, the analysis of distinct effects of different stressor groups on population health can be considered topical, as such global population stressors may leave lasting imprints on mental health at least in Western or high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Risk perception of COVID-19 was thus proposed, initially to explain the impact of viruses on people taking preventive public health measures ( Dryhurst et al, 2020 ). The more people know about COVID-19, the more they perceive the risk of viral infection and change social behavior ( Reznik et al, 2021 ), as well as examine COVID-19′ s effect on people’ s concerns about the state of the environment ( Gong and Sun, 2020 ). Many results confirm that perceived risk to COVID-19 is significantly associated with the likelihood of taking protective and preventive measures such as self-isolation and wearing a mask; this confirms the role of risk perception in influencing people's behavior ( O’ Connor and Assaker, 2021 ).…”
Section: Introductionmentioning
confidence: 99%